Contribuição do programa unidade amiga da primeira infância para melhoria do acompanhamento de crianças na atenção primária à saúde - Silva, Nádia Maria de Luna (2022)
This study aimed to analyze the data about the UAPI Program that is developed in the health units of the city of Fortaleza-Ceará that made the adhesion. Having as main guidelines of the ESF the integral care to the individual and a more integral conception of the health and disease process, which includes the attention to the child. In this sense, it is essential to understand how the PHC Health Units in Fortaleza-Ceará are dealing with these issues related to the health of children in early childhood. The research sought to characterize the contribution of the UAPI program in the monitoring of children in the UAPS who joined the program in the city of Fortaleza-Ce. The target audience of the research were children under six months old belonging to the area ascribed to the Health Units that joined the UAPI Program, given that the primary object of the research is to improve the health monitoring of these children in Primary Care. In addition, seven managers of units participating in the UAPI program participated in the research, the data were collected through an interview with the managers of the PHC units, containing questions to characterize the UAPI program in the monitoring of early childhood, through a script with four structured questions. Methodology: The research was carried out through an evaluative, cross-sectional, descriptive and documentary study with secondary data collection. The indicators for the evaluation of the Program were defined based on the guidelines applied to the monitoring of children's growth and development proposed by the UAPI Program, which were built with the objective of strengthening childcare actions within the UAPS in the city of Fortaleza. Quantitative data were analyzed using the R software (version 4.0.3), using the dplyr packages for data processing and management, lubridate for calculating the time frames and age of the participants, as well as the car package for performing the ANOVA analyzes of repeated measures, in addition, frequency analyzes were performed (centrality and dispersion trend), the adopted significance level was 5% (p≤0.05) and the analysis of the interviews was performed using the IRAMUTEQ software. Results and Discussions: as a result of the analyses, it becomes possible to understand that, even in a still timid way, health in the city of Fortaleza has been making efforts to provide a quality service to its clientele, with emphasis on early childhood. These strategies seek to favor children and health care, involving management and workers/professionals who make up the municipal health network. The research made it possible to understand that the limitations and difficulties that are found in the field regarding the implementation of the program happen not only within the scope of the unit. More studies are needed to identify whether the failures are in the implementation process, in the sphere of management, the community or health workers, and if the mishaps presented are due to the lack of personnel, structure, or even inputs or resources financial.